1996
DOI: 10.1111/j.1939-1676.1996.tb02066.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hetastarch on Serum Colloid Oncotic Pressure in Hypoalbuminemic Dogs

Abstract: The purpose of this study was t o determine the duration of action of a single dose of hetastarch. a synthetic colloid, in hypoalbuminemic dogs. Thirty hypoalbuminemic dogs (albumin concentration, 52.0 g/dL) received l dose of hetastarch each, with an average dose of 18.1 mL/kg. Doses ranged from 7.7 t o 43.9 mL/kg, with the majority of doses (n = 26) in the range of 10 t o 25 mL/kg. Dogs were allotted t o one of several groups: all dogs, dogs with acute gastrointestinal protein loss, dogs with chronic gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 13 publications
0
41
0
2
Order By: Relevance
“…Basically, the perfusion of fluid with high oncotic pressure is supposed to better fill the vascular system, adding to the given volume a proportion of volume expanded from extravascular tissue. 4,5 As a result, a smaller fluid volume has to be given to achieve adequate vascular fluid replacement. This wellacknowledged concept is supported by physiology, because plasma contains a large amount of proteins, particularly albumin, creating a physiological oncotic pressure of approximately 25 mm Hg.…”
mentioning
confidence: 99%
“…Basically, the perfusion of fluid with high oncotic pressure is supposed to better fill the vascular system, adding to the given volume a proportion of volume expanded from extravascular tissue. 4,5 As a result, a smaller fluid volume has to be given to achieve adequate vascular fluid replacement. This wellacknowledged concept is supported by physiology, because plasma contains a large amount of proteins, particularly albumin, creating a physiological oncotic pressure of approximately 25 mm Hg.…”
mentioning
confidence: 99%
“…When a significant increase in COP occurs after hetastarch administration, the increase occurs rapidly after administration and dissipates quickly. One study in hypoalbuminemic dogs reported that COP had returned to pre‐infusion values 12 hours after hetastarch administration (Moore & Garvey 1996). At 24 hours post‐infusion there was no difference in COP either between groups or within a group compared to the baseline in our study.…”
Section: Discussionmentioning
confidence: 92%
“…2001) so it just dilutes out the plasma proteins, hence causing the decrease in COP. Previous studies have shown either no change in COP (Muir & Wiese 2004) or a modest impact on COP (Smiley & Garvey 1994; Moore & Garvey 1996; Chan 2008) after administration of hetastarch. The COP of 6% hetastarch as used in this study is reported to be 32.7 ± 0.2 mmHg (Chan et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, this refers to plasma colloid concentrations and not to the duration of plasma volume expansion. In hypoalbuminaemic dogs, COP was not significantly different from baseline 12 hours after the infusion of hydroxyethyl starch (Moore & Garvey 1996) and this may occur because equilibration of COP is often rapid: interstitial fluid is drawn into, or retained in, the intravascular space by colloidal particles. Gelatins have a duration of action that is shorter than other colloids and often only just longer than crystalloids.…”
Section: Intravascular Volume Expansionmentioning
confidence: 99%
“…Hydroxyethyl starch limits peripheral oedema and ascites in hypoalbuminaemic dogs (Smiley & Garvey 1994). However, it is important to diagnose and treat underlying causes of hypoproteinaemia rather than indiscriminately administer palliative colloid therapy, because this may be ineffective if there are large ongoing losses (Moore & Garvey 1996) and there may be risks. While albumin supplementation is recommended in people because low serum albumin concentration is held to indicate a poor prognosis, most investigations of clinical albumin supplementation have failed to demonstrate a beneficial effect.…”
Section: Hypoproteinaemiamentioning
confidence: 99%